Propuesta de Implementación de la metodología Lean Manufacturing en las lineas de producción del proceso fabricación y ensamble de neveras industriales de la empresa Imbera Colombia (2022)
This work is developed under the concept of continuous improvement, generating a proposal for the implementation of lean manufacturing tools, focused on the assembly lines of industrial refrigerators of the company Imbera Colombia, identifying the opportunities presented in the process. Since they significantly affect productivity and delivery satisfaction to customers.